KEPEMILIKAN ULTIMAT, TINGKAT RISIKO, EFISIENSI DAN KINERJA PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Indria Puspitasari Lenap; Nina Karina Karim; Elin Erlina Sasanti (Jurnal Riset Akuntansi, 2018)
The aim of this paper is to define ultimate ownership and empirically verified the differences of risk rate, efficiency and performance on Shari’ah Banking Industry with ultimate ownership held by Indonesian national governmental banks, local governmental banks, block shareholding private insititutions, concentrated private banks, mixed foreign and domestic banks, foreign banks and family banks. This research object is Shari’ah Banks were listed in Indonesian Stock Exchange in the year of 2015-2017, with 36 observation unit. The data shown that the concentrated private and foreign banks, mixed foreign and domestic banks and family banks as ultimate ownership hold 75% ownership, whereas Indonesian national governmental banks and local governmental banks only have 25% ownership. This finding according to Claessens et al. (2000), Siregar (2008), Abbas et al. (2009), Surifah (2011), Chalid (2013), Susilowati and Sanjaya (2015), Lingmin (2016), Novado and Hartomo (2017). Conversely with Faccio and Lang (2002). Using statistical analysis Kruskal Wallis Test, We found the differences in risk rate (measured by FDR and CAR), efficiency (measured by NIM) and performance (measured by ROE). Based on risk rate, efficiency and general banking performance. The best banks performance are concentrated private banks. The determine of these results were strict supervision by shareholders, maanger competency, company reputation and large flow of funds. Otherwise, local governmental banks are the worst. We identify the determine of these results were the lack of supervision from government as a shareholders, incompetent management, less of inovation and promotion and low of aggressiveness to attract the customer. Keywords : Shari’ah Banks, Ultimate Ownership, Risk Rate, Efficiency, Performance.